Implementación de una máquina para grabado rápido sobre tela para el Laboratorio de fabricación de la Universidad Politécnica Salesiana - Godoy Vásquez, Jairo Eduardo (2016)
This document describes the performance of a laser engraving machine on cloth named "MACMEL" (Laser Engraving Machine on Clothes in Arduino Mega) as an alternative to fancywork technique and improve the work of cutting and making at accessible cost, plus it can be a help to rapid prototyping in the Fabrication Laboratory of Salesian University. MACMEL serves for the labeling of clothing, in order to identify the clothing of children, the older adult and people with disabilities. The Fabrication Laboratory contemplates its use by students in order to: label their aprons, labeling of vinyl labels for projects and manufacture of masks for depositing solder paste on PCBs. MACMEL's controller is a board Arduino MEGA 2560 that through the RAMP 1.4 shield card enables control of XY positioning system and the laser module of maximum power 2.5W, your power is regulated by G-codes, is selected a semiconductor laser for its affordable price. The application software is on a personal computer and sends the list of instructions for the laser engraving to MACMEL in G-codes obtained from the processing of an image in Inkscape and post-processed in a text editor. In the fabrication laboratory were performed tests to calibrate the MACMEL. It is written a user manual that containing a catalog of engravings.